1997
DOI: 10.1086/310464
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Synthesis of Molecular Hydrogen on Surfaces of Astrophysical Interest

Abstract: We report on the first results of experiments to measure the recombination rate of hydrogen on surfaces of astrophysical interest. Our measurements give lower values for the recombination efficiency (sticking probability S x probability of recombination upon H-H encounter γ) than model-based estimates. We propose that our results can be reconciled with average estimates of the recombination rate (1/2n H n g v H ASγ) from astronomical observations, if the actual surface of an average grain is rougher, and its a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
225
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(229 citation statements)
references
References 19 publications
3
225
0
1
Order By: Relevance
“…Garrod et al (2007) have previously proposed a formula in their models that can be used to describe the chemical desorption (or reactive desorption). They derived the probability of A24, page 4 of 6 Bergeron et al (2008); (c) Al-Halabi & van Dishoeck (2007), Amiaud et al (2007); (d) Pirronello et al (1997); (e) Amiaud et al (2006) for low coverage; ( f ) Minissale et al (2015); (g) Dulieu et al (2013); (h) Speedy et al (1996), Fraser et al (2001 energy derived of 5800 K with pre-factor of 10 15 s −1 here corrected to have a pre-factor of 10 12 s −1 ; (i) Noble et al (2012a); ( (2)) that include division between the degree of freedom and the fraction of kinetic energy after bounce ( is mass dependent). In red we show the equal share of energy and the constant value of .…”
Section: Theoretical Estimate Of the Desorption Efficiencymentioning
confidence: 99%
“…Garrod et al (2007) have previously proposed a formula in their models that can be used to describe the chemical desorption (or reactive desorption). They derived the probability of A24, page 4 of 6 Bergeron et al (2008); (c) Al-Halabi & van Dishoeck (2007), Amiaud et al (2007); (d) Pirronello et al (1997); (e) Amiaud et al (2006) for low coverage; ( f ) Minissale et al (2015); (g) Dulieu et al (2013); (h) Speedy et al (1996), Fraser et al (2001 energy derived of 5800 K with pre-factor of 10 15 s −1 here corrected to have a pre-factor of 10 12 s −1 ; (i) Noble et al (2012a); ( (2)) that include division between the degree of freedom and the fraction of kinetic energy after bounce ( is mass dependent). In red we show the equal share of energy and the constant value of .…”
Section: Theoretical Estimate Of the Desorption Efficiencymentioning
confidence: 99%
“…Burke and Hollenbach (1983), Hollenbach and McKee (1989), and Buch and Zhang (1991) make theoretical estimates of the T and T gr dependence of S and . Lin and Vidali (1996) and Pirronello et al (1997aPirronello et al ( , 1997b have recently reported new laboratory measurements of S.…”
Section: H 2 Formation Destruction and Heatingmentioning
confidence: 99%
“…In the experiments of Pirronnello et al, [16][17][18] a model grain surface was irradiated with a beam of H and D atoms and HD molecules were produced. A temperature scan was performed, and the results were analyzed in terms of rate equations.…”
Section: Resultsmentioning
confidence: 99%